Evaluation of lustre and physical attributes of wool in Marwari and Nali sheep breeds* - SHARMA, M K; SINGH, V K; BENIWAL, B K; MEHTA, S C; GAHLOT, R S (The Indian Journal of Animal Sciences, 2013)
Marwan and Nali are two important carpet wool producing breeds of sheep in India. The wool ofNali breed was more lustrous and finar thun that of Marwari. The least-squares means for wool quality traits i.e. tenacity, extension, reflectance, fluoresccnce, total, ratio, diameter and medullation of wool fibre have been estimated to be 6.48+-0.167 g/tex, 23.3 7+-0.53%, 176.43+-3.899 vr, 111.20+-2.664 vT, 287.79±6.402 T, 1.08±0.103, 32.91±0.528 u and 51.42±2.052% in Marwari and 6.42±0.144 g/tex, 21.55±0.464%, 215.67±3.359 vr, 140.08±2.295 vT, 355.67±5.516 ;T1 0.6±0.088, 28.33±0.4551-1 and 50.80±1.7G8% in Nali. The heritability estimates for tenacity, extension, reflectance, fluorescence, total (r+f) and medullation revealed that all the traits had moderate to high heritability, indicating that phenotypic selection for individual trait would be quite effective. The phenotypic correlations among the quality traits indicate that the selection index would be a better choice if simultaneous selection in quality traits is desired.